Service Process Excellence in Public Services - László Buics; Edit Süle (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
The goal of this paper is to create a comprehensive picture of the service process structure of a typical Hungarian Government Window, which functions as a one-stop shop service centre for administrative public services. The research is focusing on process management details regarding service quality, and excellence in public services. Performance indicators are identified through a literature review based on the similarities and differences of private and public services. We are using collected data from a Government Window to visualize front office operations with Business Process Modelling and we analyse the time-related data by using performance metrics identified in service quality literature. Our research provides useful insights into the Hungarian public service centre operations that can be useful as a basis of comparison with other countries' similar service systems.
Keywords: H83; 330; Business Process Modelling; Key Performance Indicators; public service processes; Unified Services Theory; one-stop shops